IMPLEMENTASI PERATURAN BUPATI NOMOR 57 TAHUN 2017 TENTANG SISTEM INFORMASI DESA DI DESA GERINGGING JAYA KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2018-2020 - Hizbullah, Teguh; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Kuantan Singingi Regency is one of the regencies that implement the SID program in 12 empowerment program contained in the regulation of the Regent of Kuantan Singingi Regency. This program is a set of tools and processes for utilizing data and information to support resource management at the village level. The purpose of this study was to find out how the Implementation of the Village Information System (SID) Program in Sentajo Raya District, Kuantan Singingi Regency and the factors that hindered it. The theory used is the theory of Donald Van Meter and Carl. E. Van Horn, namely there are six indicators that affect implementation: Standards and policy objectives; Resource; Inter-organizational communication and strengthening of activities; Characteristics of implementing agents; Social, economic and political conditions; and disposition of the implementor. This research uses qualitative research and the required data, both primary and secondary, are obtained through interview, observation and documentation techniques for further analysis using interactive data analysis techniques. The results of this study indicate that: first, the implementation of the Village Information System Program (SID) in Sentajo Raya District, Kuantan Singingi Regency is not optimal. Second, the factors that hinder the implementation of the Village Information System Program (SID) in Sentajo Raya District,  Kuantan Singingi Regency, namely: human resources, policy resources, communication between organizations and strengthening activities, assessment of target groups (public opinion), economic conditions, economic conditions politics and cognition of the implementor/understanding of the implementor.  Keywords: Village Information System, Public Policy, Implementation, Program